“We’re human beings’ tamers”: pacification, necropolitics and civilization in the favelas of Río de Janeiro. - Saborío Rodríguez, Sebastián (2019)
This article analyses the Pacifying Police Units (UPPs) of Rio de Janeiro which, since 2008, have taken control of some of the favelas that were previously dominated by highly armed criminal groups. Through both Mbembe’s concept of “necropolitics” and Neocleous’ one of “pacification”, it will be demonstrated that in these spaces po- lice control is strongly marked by its colonial past. In particular, during the last forty years it has become clear that, for those who have governed the city, the life of the inhabitants of the favelas has no value by itself and that the decision of letting them live or die is subordinated to economic interests. Before the pacification process, local authorities, supportedby public opinion, encouraged police lethality within the favelas, while the UPPs’ presence was characterized by an attempt to hide police’s necropower in these territories and by the willingness to transform the image of the residents with the intention of supporting processes of attraction of international capital that the city had implemented in the last decade. To conclude, the article will look into the reasons that brought UPPs’ agents to consider that their main mission is that of “civilizing” the favela population. The analysis proposed in this article is the result of an ethnographic study mainly developed with members of three different Pacifying Police Units between 2013 and 2015.